Pengaruh Kompetensi Tenaga Penjual, Kualitas Pelayanan, Penanganan Komplain, dan Citra Perusahaan Terhadap Loyalitas Nasabah Asuransi - Ramadhani, Ela; Maidalena, Maidalena; Ahmadi Bi Rahmani, Nur (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
The purpose of this study was to investigate the effect of salesperson competence, service quality, complaint handling and company image on customer loyalty at PT AJS Bumiputera Medan City Branch. The research was conducted using primary data. The population in this study were all employees of PT AJS Bumiputera Medan City Branch totaling 238 customer with the technique used purposive sampling, namely a sample of 70 respondents. The data collection used a questionnaire. Testing using multiple linear regression analysis and classical assumption tests and data quality tests. The results of the study concluded that service quality, salesperson competence and customer image have a positive effect on customer loyalty, and complaint handling has a negative effect on customer loyalty in PT AJS Bumiputera Medan City Branch . Simultaneously salesperson competence, service quality, complaint handling and company image affect customer loyalty where F count 13.069 > F tabel 2,511. Then the R Square value is 0.446 or 44.6%.